1989
DOI: 10.1002/ijc.2910440409
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of gastric cancer and diet in Italy

Abstract: A case-control study was conducted in high- and low-risk areas of Italy to evaluate reasons for the striking geographic variation in gastric cancer (GC) mortality within the country. Personal interviews with 1,016 histologically confirmed GC cases and 1,159 population controls of similar age and sex revealed that the patients were more often of lower social class and resident in rural areas and more frequently reported a familial history of gastric (but not other) cancer. After adjusting for these effects, cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
222
7
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 453 publications
(248 citation statements)
references
References 24 publications
15
222
7
4
Order By: Relevance
“…Duration of refrigerator use or freezer use was not associated with stomach cancer risk in the Netherlands Cohort Study, in contrast with the results of casecontrol studies performed in Europe or the USA, which rather consistently reported a decreased stomach cancer risk with long-term use of a refrigerator [2,5,9,16,18,38,54]. Three of the case-control studies did not find an association [15,44,47] and no other cohort study reported on this association.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Duration of refrigerator use or freezer use was not associated with stomach cancer risk in the Netherlands Cohort Study, in contrast with the results of casecontrol studies performed in Europe or the USA, which rather consistently reported a decreased stomach cancer risk with long-term use of a refrigerator [2,5,9,16,18,38,54]. Three of the case-control studies did not find an association [15,44,47] and no other cohort study reported on this association.…”
Section: Discussionmentioning
confidence: 67%
“…Overall, in the majority of case-control studies, positive associations were observed for (total) salt or sodium intake [2,3,33,34], consumption of salted fish, salted meat, pickles and soup [5,7,16,[34][35][36][37][38][39][40], adding salt to food at dinner [5,9,41], preference of salty foods [4,5,11,40,42]. The relative risks reported ranged from 1.5 to 6.7 for various measures of salt intake [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inverse association was particularly evident for aggressive types of prostate cancer and for men not taking a b-carotene supplement (Gann et al, 1999). Several epidemiologic studies have also reported an inverse association between tomato intake and the risk of gastric cancer (La Vecchia et al, 1987;Buiatti et al, 1989;Hansson et al, 1993). Epidemiological observations also report an inverse association between plasma or tissue lycopene levels and the incidence of CVD.…”
Section: A Basu and V Imrhanmentioning
confidence: 99%
“…Epidemiological studies show that enhanced garlic consumption is closely related with reduced cancer incidence (Haenszel et al, 1972;Buiatti et al, 1989). Dially disulfide (DADS), an oil-soluble organosulfur compound in processed garlic, inhibited the proliferation of human colon, lung, and skin cancer cells Milner, 1996a, Sundaram andMilner, 1996b).…”
Section: Introductionmentioning
confidence: 99%